RANCANG BANGUN MEDIA PEMBELAJARAN DENGAN PENDEKATAN MASALAH TERBUKA MENGGUNAKAN WEB UNTUK PENINGKATAN BERPIKIR KRITIS SISWA SMK - Renra Noviana, Renra (2020)
Basic programming is a vocational school subject that requires critical thinking skills, there are still many students who have trouble against learning programming, observation results show that there are problems in the learning process of basic programming which results in difficulties in learning other programming fields. The proposed solution to overcome this problem is by increasing student's critical thinking skills with learning media that uses open ended approach. The open ended approach allows students to think broadly by combining their own knowledges or ways of thinking that have been previously learned. This study aims to develop instructional media with an open ended approach measure the improvements on students from the application of media and student responses to the media. This study uses a Comprehensive Life Cycle methodology to develop media. One-group pretest-postest was used for the research design. media with an open problem approach have been developed and get a percentage score of 86% or "very good" by experts on media testing and get a percentage score of 85% or "very good" by experts on material testing. The use of media with an open ended approach can improve critical thinking skills with the increase in students' cognitive tests with the High Order Thinking Skill (HOTS) category questions with an increase in the average N-gain of students by 0.46 (which is in the "medium" category). Student responses to learning media get a percentage score of 75%.